Changes in land use practices influence soil sulfur fractions and their bioavailability - Padhan, Dhaneshwar; Rout, Pragyan Paramita; Sen, Arup (Frontiers in Sustainable Food Systems, 2023)
Changes in land use practices may influence the distribution of soil sulphur (S) fractions and its bioavailability. Therefore, the study was undertaken to assess the influence of different land use changes on the distribution of soil S fractions and its bioavailability for plant nutrition. Soil samples from farmer's fields with different land use practices such as rice-mustard-jute (R-M-J), rice-lentil-jute (R-L-J), rice-lentil-sesame (R-L-S), rice-vegetable-jute (R-V-J) and rice-potatogreen gram (R-P-G) were collected and analyzed for different fractions of S. Bioavailability of S was assessed by extracting the soil with six different extractants (acidic, neutral and alkaline) having different mode and chemistry of extraction. The results showed that changes in land use practices could influence the distribution of soil S fractions and its bioavailability. Organic S was the dominant fraction accounting 93.5% of total S across the land use practices. The inorganic S fraction (water-soluble, sorbed and occluded) varied significantly among the land use practices.Amongst the inorganic fraction, water-soluble fraction was the dominant fraction across the land use. The bioavailability of S assessed through different chemical extractants followed the order sodium hydrogen carbonate (NaHCO3)> mehlich-3> ammonium bicarbonate-diethylenetriamine pentaacetic acid (AB-DTPA)>ammonium acetate-acetic acid (NH4Ac-HOAc)>calcium dihydrogen phosphate Ca(H2PO4)2> calcium chloride (CaCl2). By establishing the relationships between extractable S with soil S fractions, it was observed that all the extractants could extract S from the water-soluble, sorbed and organic S fractions with little extractability from the occluded fraction. Amongst the extractants tested, the mehlich-3 extracted a similar amount of S corresponding to inorganic fraction across the land use. Also, it maintained positive relationships